Multiproxy analysis exploring patterns of diet and disease in dental calculus and skeletal remains from a 19th century Dutch population - Bartholdy, Bjørn Peare; Hasselstrøm, Jørgen B.; Sørensen, Lambert K.; Casna, Maia; Hoogland, Menno; Historisch Genootschap Beemster; Henry, Amanda G. (Peer Community Journal)

(untitled)
Dental calculus is an excellent source of information on the dietary patterns of past populations, including consumption of plant-based items. The detection of plant-derived residues such as alkaloids and their metabolites in dental calculus provides direct evidence of consumption by individuals within a population. We conducted a study on 41 individuals from Middenbeemster, a 19th century rural  Dutch archaeological site. Skeletal and dental analysis was performed to explore potential relationships between pathological lesions and presence of alkaloids. Dental calculus was analysed using ultra-high-performance liquid chromatography-tandem  mass spectrometry (UHPLC-ESI-MS/MS). We were able to detect nicotine, cotinine, caffeine, theophylline, and salicylic acid, suggesting the consumption of tea and coffee and smoking of tobacco on an individual scale, which is also confirmed by historic documentation and identification of pipe notches in the dentition. Nicotine and/or cotinine was present in 56% of individuals with at least one visible pipe notch. There is some influence of skeletal preservation on the detection of alkaloids, with higher quantities of compounds extracted from well-preserved individuals, and we observe a positive relationship between weight of the calculus sample and quantity of detected compounds, as well as between chronic maxillary sinusitis and the presence of multiple alkaloids. There are many limitations that will need to be addressed going forward with this type of analysis; we stress the need for more systematic research on the consumption of alkaloid-containing items and their subsequent concentration and preservation in dental calculus, in addition to how mode of consumption may affect concentrations in the dentition. Despite the limitations, this preliminary study illustrates many benefits of using calculus to target a variety of compounds that could have been consumed as medicine or diet. This method allows us to directly address specific individuals, which can be especially useful in individuals that are not always well-documented in historic documentation, such as rural populations, and especially children and women.